2023
DOI: 10.26719/emhj.23.038
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of knowledge, attitude, behaviour and preventive measures for COVID-19 infection in Lebanon

Abstract: Background: The World Health Organization has reinforced its recommendation to maintain preventive measures for COVID-19. The success of preventive measures is largely dependent on public attitudes and knowledge. Aims: This study aimed to assess the relationship between knowledge, attitude, risky behaviours and preventive measures and coronavirus 19 (COVID-19) infection in the Lebanese population. Methods: This cross-sectional study was conducted during September–October 2020 using the snowball sampling techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Various obstacles to PCR testing at the individual, cultural, environmental, and financial levels were faced by Syrian refugees in Lebanon. 15 The barriers identified in this study and others were mainly related to individuals' perceptions of lack of need or lack of affordability, 15,26 despite the availability of free testing services and the national effort to raise awareness. 15 Perceived stigma, discrimination, fear of deportation, and limited accessibility to testing centers were reported as additional barriers to testing among Syrian refugees in Lebanon.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Various obstacles to PCR testing at the individual, cultural, environmental, and financial levels were faced by Syrian refugees in Lebanon. 15 The barriers identified in this study and others were mainly related to individuals' perceptions of lack of need or lack of affordability, 15,26 despite the availability of free testing services and the national effort to raise awareness. 15 Perceived stigma, discrimination, fear of deportation, and limited accessibility to testing centers were reported as additional barriers to testing among Syrian refugees in Lebanon.…”
Section: Discussionmentioning
confidence: 85%
“…The first study was based on a self-reported outcome and found a prevalence of 13.9% out of 1,119 participants, with a higher risk of infection among older adults. 26 The second study was based on lateral flow test and found a crude seroprevalence of 16.0%, with a slightly higher prevalence among those aged 60 years or older (18.5%). However, no statistically significant difference was found between the age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional counseling and education are considered to be successful tools in raising awareness, supporting healthy behaviors and emphasizing NK (Sakr et al , 2022e, 2023b). Hence, nutritional counseling will create a nutrition strategy that will assist people in obtaining the nutrients they require to sustain a healthy lifestyle (Coppoolse et al , 2020; Perlstein et al , 2016; Ohtsuki et al , 2018).…”
Section: Introductionmentioning
confidence: 99%